In the Shadow of Violent Men: Emancipation and Moral Autonomy in The Last of Us and The Last of Us Part II - D'Amato, Claudio (Loading)

(untitled) (Canadian Game Studies Association, 2025)
This paper offers an interpretation of The Last of Us and The Last of Us Part II as narratives of moral emancipation from patriarchal structures. It argues that the protagonists, Ellie and Abby, participate in the construction of each other’s moral agency and autonomy, while navigating their complex gender identities and attempting to break the cycles of violence and retaliation initiated by their fathers. Neither character succeeds in the end. Indeed, the games’ main argument is that if moral autonomy is ever within reach, it is not on individualistic or universalistic terms; that is, that the notion itself of being autonomous is necessarily relational, gradual, and situated within the gender politics of each character’s moral particularity.